Analisis Faktor-Faktor Yang Mempengaruhi Intergritas Laporan Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Purba, Hasian (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Publication of financial reports as accounting information products produced by the company, cannot be separated from the process of its preparation. The purpose of this study is to find empirical evidence of the influence of the Financial Report Integrity variable on Independent Commissioners, Institutional Ownership, Financial Distress, KAP Reputation and Auditor Industry Specialization. The research method used in this research activity uses the following research characteristics: Mixed Research Method refers to a combination of quantitative and qualitative methods. The population in this study were manufacturing companies for the 2019-2022 period on the Indonesia Stock Exchange. Based on the analysis of variable data, Independent Commissioners partially do not have a significant influence on the integrity of financial reports. Based on data analysis, the institutional ownership variable partially does not have a significant influence on the Integrity of Financial Reports.